1996
DOI: 10.1212/wnl.47.2.477
|View full text |Cite
|
Sign up to set email alerts
|

Corpus callosum morphology in children with Tourette syndrome and attention deficit hyperactivity disorder

Abstract: The aim of this study was to investigate the morphology of the corpus callosum (CC) in Tourette syndrome (TS) and attention deficit hyperactivity disorder (ADHD) to determine whether these conditions affect distinct regional differences. Seventy-seven children and adolescents, aged 6 to 16 years, comprised the four research groups--16 patients with TS, 21 patients with TS plus ADHD, 13 patients with ADHD, and 27 unaffected control subjects. A semiautomated, computer-assisted procedure was used to measure the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
132
2
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(148 citation statements)
references
References 7 publications
11
132
2
3
Order By: Relevance
“…A prior MRI study in children with ADHD found reductions in anterior corpus callosum area, which was significantly correlated with impulsivity-hyperactivity subscales of both the parent and teacher Conner's Questionnaire (Giedd et al, 1994). Other studies have found reductions in anterior corpus callosum volume in children with ADHD (Hynd et al, 1991), (Baumgardner et al, 1996). However, another larger MRI study did not find smaller corpus callosum volumes in ADHD children (Castellanos et al, 1996), possibly because this study did not control for position of the brain (Giedd et al, 2001).…”
Section: Discussionmentioning
confidence: 54%
“…A prior MRI study in children with ADHD found reductions in anterior corpus callosum area, which was significantly correlated with impulsivity-hyperactivity subscales of both the parent and teacher Conner's Questionnaire (Giedd et al, 1994). Other studies have found reductions in anterior corpus callosum volume in children with ADHD (Hynd et al, 1991), (Baumgardner et al, 1996). However, another larger MRI study did not find smaller corpus callosum volumes in ADHD children (Castellanos et al, 1996), possibly because this study did not control for position of the brain (Giedd et al, 2001).…”
Section: Discussionmentioning
confidence: 54%
“…Any disturbance or anomalies in the CC can result in certain neurologic disorders. [30][31][32][33] Nevertheless, in the present work, the population between 2 and 5 years of age included only 7 children, a quite small sample size. A study with a larger number of subjects would be necessary to extract more reliable conclusions.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, studies of clinical groups highlight the parallel developmental differences in these related systems. For example, compared to age-related controls, children with ADHD demonstrate smaller midsagittal anterior corpus callosum areas (Baumgardner et al, 1996), as well as reduced premotor, prefrontal (Mostofsky, Cooper, Kates, Denckla, & Kaufmann, 2002), and cerebellar volumes (Mostofsky, Reiss, Lockhart, & Denckla, 1998). At the same time, children with ADHD also show reduced motor speeds (Denckla, 1973;Mahone, Prahme, Koth, Morris, & Denckla, 2004;Schuerholz, Cutting, Mazzocco, Singer, & Denckla, 1997), increased motor overflow (Mostofsky, Newschaffer, & Denckla, 2003), and decreased motor inhibition (Mahone et al, 2006;Wodka et al, in press).…”
Section: Discussionmentioning
confidence: 99%